The Investigation of the Effect of Polypropylene Waste on the Compressive Strength of Iraqi Portland Cement (UM-Qasir) - Nadhim A. Abdullah; Mohammed A. Jaber; Hamed A. Hamdi (Genius Journals, 2023)
The present study includes inspecting the change of compressive strength of the Ordinary Iraqi Cement (henceforth; OIC) produced by Um- Qasir plants. The used cement was a petrified type, which was obtained by direct exposure to environmental circumstances for three months. The study was carried out by using a cubic mold of 50 mm in length for mortar and 150 mm for concrete, where the mixing ratio was: 1 cement, 1.5 sand, and 3 gravel. Polypropylene fibers waste was added in the form of square nets with a 40mm of side dimension. The added nets ratio range was (0-4), and three types of curing were used: Moisture, Water, and Air. All cement samples were measured within seven days of curing aging, while the concrete samples were measured after 28 days. Furthermore, the study incorporated the effect of changing sand particle size. Water Curing was the best curing condition for mortar samples where the compressive strength varies within a range of (10-14.12) N/mm2. According to the curing method (Dry, Wet, and Moisture). The number of nets of polypropylene waste added is also has affected the compressive strength where a 15.42 N/ mm2 was obtained at two added nets of polypropylene at wet curing. The effect of sands was also studied by using two different particles size, which (600 micrometers and 1.2 millimeters) and the obtained results showed that the smallest particle size is the better compressive strength. Finally, a comparison between petrified and non-petrified cement of concrete was studied. The obtained results showed a rapid decrease in compressive strength: (7.11 N/ mm2) and (18.4 N/ mm2) for petrified and non-petrified cement respectively
Keywords: UM-Qasir; Iraqi; compressive strength